2003
DOI: 10.1146/annurev.biophys.32.110601.142445
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dynamics in Enzyme Activity

Abstract: Although protein function is thought to depend on flexibility, precisely how the dynamics of the molecule and its environment contribute to catalytic mechanisms is unclear. We review experimental and computational work relating to enzyme dynamics and function, including the role of solvent. The evidence suggests that fast motions on the 100 ps timescale, and any motions coupled to these, are not required for enzyme function. Proteins where the function is electron transfer, proton tunneling, or ligand binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
340
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(350 citation statements)
references
References 140 publications
6
340
1
2
Order By: Relevance
“…It has been shown that distributed mutations can contribute significantly to the tuning of pK a values. 40,44,45 Dynamic effects are known to play a role in enzyme catalysis [41][42][43]46 , although the precise effect and magnitude of their contributions remains controversial 2,3 . At the very least, an enzyme active site has to be deformable to maintain complementarity to the various species along the reaction coordinate [41][42][43] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that distributed mutations can contribute significantly to the tuning of pK a values. 40,44,45 Dynamic effects are known to play a role in enzyme catalysis [41][42][43]46 , although the precise effect and magnitude of their contributions remains controversial 2,3 . At the very least, an enzyme active site has to be deformable to maintain complementarity to the various species along the reaction coordinate [41][42][43] .…”
Section: Discussionmentioning
confidence: 99%
“…2000; Tarek & Tobias 2000Teeter et al 2001;Caliskan et al 2002;Paciaroni et al 2002). Highly viscous solvents, such as trehalose, suppress dynamical transition behaviour (Hagen et al 1995;Cordone et al 1999;Walser et al 2000), and neutron-scattering experiments on enzymes in a range of cryosolvents showed that the dynamical transition behaviour of the protein solution resembles that of the pure solvent (Bizzarri et al 2000;Reat et al 2000;Daniel et al 2003).…”
Section: Solvent Role In the Protein-glass Transitionmentioning
confidence: 99%
“…ions) are exchanged between water and amino acids in the proteins (Tsui et al 1999;Eyles and Kaltashov 2004;Pan et al 2010;Chen et al 2010;Gruebele 2010). However, a detailed understanding of folding is still missing due to the high dimensionality of the protein conformational spaces and by the wide range of relevant time scales (Daniel et al 2003).…”
Section: Introductionmentioning
confidence: 99%